Cortico-cortical and thalamo-cortical connectivity during non-REM and REM sleep: Insights from intracranial recordings in humans. (November 2022) - Lambert, Isabelle; Roehri, Nicolas; Fayerstein, Julie; Giusiano, Bernard; Colombet, Bruno; Bénar, Christian-George; Bartolomei, Fabrice
Highlights: Brain connectivity dramatically changes during sleep stages and wakefulness. Cortico-cortical connectivity is predominant during slow wave sleep. Thalamo-cortical connectivity is critical during Rapid Eye Movement sleep and involves the insula. Abstract: Objective: To study changes of thalamo-cortical and cortico-cortical connectivity during wakefulness, non-Rapid Eye Movement (non-REM) sleep, including N2 and N3 stages, and REM sleep, using stereoelectroencephalography (SEEG) recording in humans. Methods: We studied SEEG recordings of ten patients during wakefulness, non-REM sleep and REM sleep, in seven brain regions of interest including the thalamus. We calculated directed and undirected functional connectivity using a measure of non-linear correlation coefficient h 2 . Results: The thalamus was more connected to other brain regions during N2 stage and REM sleep than during N3 stage during which cortex was more connected than the thalamus. We found two significant directed links: the first from the prefrontal region to the lateral parietal region in the delta band during N3 sleep and the second from the thalamus to the insula during REM sleep. Conclusions: These results showed that cortico-cortical connectivity is more prominent in N3 stage than in N2 and REM sleep. During REM sleep we found significant thalamo-insular connectivity, with a driving role of the thalamus. Significance: We found a pattern of cortical connectivity during N3 sleep concordant with antero-posterior traveling slow waves. The thalamus seemed particularly involved as a hub of connectivity during REM sleep.